Human Toll like receptor 4 gene expression of PBMCs in diabetes mellitus type 2 patients - Sepehri, Z; Kiani, Z; Nasiri, A A; Mashhadi, M A; Javadian, F; Haghighi, A; Kohan, F; Bahari, A; Sargazi, A (Cellular and Molecular Biology, 2015)
Toll like receptor 4 (TLR4) is one of the most pivotal pathogen recognition receptors (PRRs) in innate immune systems. In this study, we evaluate the expression of the TLR4 in patients with diabetes mellitus type 2 (DM2) in comparison to healthy controls. Expression of TLR4 in 32 human peripheral blood mononuclear cells (PBMCs) of patients with DM2 and 20 control samples was assessed using Real”Time PCR technique. For each patient, body mass index (BMI) and blood glucose levels were measured. The results of Real”Time PCR showed a 5”folds increase in expression of TLR4 on the PBMCs of DM2 patients in comparison to controls. No correlation was observed between the TLR4 expression and sex or BMI. Our results confirmed that DM2 can increase TLR4 expression independent from sex, blood glucose concentrations and BMI.